Combinations of Toll-like receptor 8 agonist TL8-506 activate human tumor-derived dendritic cells. Issue 6 (10th June 2022) - He, Mi; Soni, Bhavesh; Schwalie, Petra C; Hüsser, Tamara; Waltzinger, Caroline; De Silva, Duvini; Prinz, Ylva; Krümpelmann, Laura; Calabro, Samuele; Matos, Ines; Trumpfheller, Christine; Bacac, Marina; et al.
Abstract : Background: Dendritic cells (DCs) are professional antigen presenting cells that initiate immune defense to pathogens and tumor cells. Human tumors contain only few DCs that mostly display a non-activated phenotype. Hence, activation of tumor-associated DCs may improve efficacy of cancer immunotherapies. Toll-like receptor (TLR) agonists and interferons are known to promote DC maturation. However, it is unclear if DCs in human tumors respond to activation signals and which stimuli induce the optimal activation of human tumor DCs. Methods: We first screened combinations of TLR agonists, a STING agonist and interferons (IFNs) for their ability to activate human conventional DCs (cDCs). Two combinations: TL8-506 (a TLR8 agonist)+IFN-γ and TL8-506+Poly(I:C) (a TLR3 agonist) were studied in more detail. cDC1s and cDC2s derived from cord blood stem cells, blood or patient tumor samples were stimulated with either TL8-506+IFN-γ or TL8-506+Poly(I:C). Different activation markers were analyzed by ELISA, flow cytometry, NanoString nCounter Technology or single-cell RNA-sequencing. T cell activation and migration assays were performed to assess functional consequences of cDC activation. Results: We show that TL8-506 synergized with IFN-γ or Poly(I:C) to induce high expression of different chemokines and cytokines including interleukin (IL)-12p70 in human cord blood and blood cDC subsets in a combination-specific manner. Importantly, both combinations induced the activation of cDC subsets in patient tumor samples ex vivo. The expression of immunostimulatory genes important for anticancer responses including CD40, IFNB1, IFNL1, IL12A and IL12B were upregulated on stimulation. Furthermore, chemokines associated with CD8 + T cell recruitment were induced in tumor-derived cDCs in response to TL8-506 combinations. In vitro activation and migration assays confirmed that stimulated cDCs induce T cell activation and migration. Conclusions: Our data suggest that cord blood-derived and blood-derived cDCs are a good surrogate to study treatment responses in human tumor cDCs. While most cDCs in human tumors display a non-activated phenotype, TL8-506 combinations drive human tumor cDCs towards an immunostimulatory phenotype associated with Th1 responses on stimulation. Hence, TL8-506-based combinations may be promising candidates to initiate or boost antitumor responses in patients with cancer.